2014
DOI: 10.1002/2014ja020180
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the dayside diffuse auroral intensity by the solar wind dynamic pressure

Abstract: Compared to the recently improved understanding of the nightside diffuse aurora, the mechanism(s) responsible for the dayside diffuse auroral precipitation remains limitedly understood. We investigate the dayside diffuse aurora observed by the all-sky imagers of Chinese Arctic Yellow River Station in the time interval of 02:00-10:00 UT (05:00-13:00 magnetic local time) on 2 January 2006. In this interval, the intensity of dayside diffuse aurora is highly correlated with the solar wind dynamic pressure with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…We therefore suggest that the unstructured DDAs observed in the morning are extension of the nightside diffuse aurora to the morning and are caused by scattering the plasma sheet electrons into loss cone by whistler-mode chorus waves, which are modulated both by compressional Pc 4-5 waves [Li et al, 2011a] and density variations [Li et al, 2011b] and are commonly observed in the dawn flank of the magnetosphere [Li et al, 2009]. Some recent studies found sudden increase of solar wind dynamic pressure can lead to enhancement of the unstructured DDAs [Shi et al, 2015;Liu et al, 2015]. This may presents indirect evidence for our suggestion because the compressional waves can modulate the chorus waves [Li et al, 2011b], and increase of solar wind dynamic pressure can certainly generate compressional waves in the magnetosphere [e.g., Han et al, 2007].…”
Section: Unstructured Ddas In the Morningmentioning
confidence: 83%
“…We therefore suggest that the unstructured DDAs observed in the morning are extension of the nightside diffuse aurora to the morning and are caused by scattering the plasma sheet electrons into loss cone by whistler-mode chorus waves, which are modulated both by compressional Pc 4-5 waves [Li et al, 2011a] and density variations [Li et al, 2011b] and are commonly observed in the dawn flank of the magnetosphere [Li et al, 2009]. Some recent studies found sudden increase of solar wind dynamic pressure can lead to enhancement of the unstructured DDAs [Shi et al, 2015;Liu et al, 2015]. This may presents indirect evidence for our suggestion because the compressional waves can modulate the chorus waves [Li et al, 2011b], and increase of solar wind dynamic pressure can certainly generate compressional waves in the magnetosphere [e.g., Han et al, 2007].…”
Section: Unstructured Ddas In the Morningmentioning
confidence: 83%
“…Previous studies have suggested that whistler‐mode chorus waves also contribute to the production of dayside diffuse aurora (Ni et al., 2014; Nishimura et al., 2013; Shi et al., 2012, 2014). Chorus wave induced electron precipitation is found to be strongest from the nightside to dawn sectors over 4 < L < 6.5 (Ma et al., 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…During the purely dynamic pressure enhancement or the impact of interplanetary (IP) shocks (with high dynamic pressures and southward IMFs), global auroras can be brightened gradually from the dayside to the nightside (termed "compression auroras" or "shock auroras") (Du et al, 2011;Holmes et al, 2014;Liou et al, 2007;Meurant et al, 2004;Ni et al, 2016;Nomura et al, 2016;Peng et al, 2011;Shi et al, 2014;Tsurutani et al, 2001;Yang et al, 2011;Zhou & Tsurutani, 1999;Zhou et al, 2003;Zhang et al, 2008). The large disturbances in solar wind not only directly affect the magnetospheric plasma wave intensity and the auroral brightness but also cause geomagnetic storms or magnetospheric substorms.…”
Section: Introductionmentioning
confidence: 99%